2018
DOI: 10.19044/esj.2018.v14n33p408
|View full text |Cite
|
Sign up to set email alerts
|

Impacts des changements de l’occupation du sol et des changements climatiques sur le bassin versant de la rivière Davo, Côte d’Ivoire

Abstract: The main objective of this study is to asssess the impacts of climate change and land cover change on the hydrology of the Davo river basin located in southwestern of Côte d'Ivoire. Two scenarios of climate change (A2 and B2) and two scenarios of land cover called scenario 1 (deforestation) and scenario 2 (reforestation) were established, and streamflows under these scenarios were simulated by the hydrological model CEQUEAU. Each scenario showed distinct variations in streamflows. Regarding the impacts of land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Indeed, like the forest areas of Côte d'Ivoire, the Lobo watershed is undergoing rapid deforestation due to agricultural activities[37]. Indeed, the work of[38] and[39] Journal of Water Resource and Protection on the Boubo, Agneby and Davo basins clearly showed that a reduction in vegetation cover contributes to an increase in flows. In order to assess the impact of meteorological drought on flows, a correlative analysis was carried out between meteorological (SPEI) and hydrological (SDI) drought indices at the Daloa, Vavoua and Zuénoula stations.…”
mentioning
confidence: 99%
“…Indeed, like the forest areas of Côte d'Ivoire, the Lobo watershed is undergoing rapid deforestation due to agricultural activities[37]. Indeed, the work of[38] and[39] Journal of Water Resource and Protection on the Boubo, Agneby and Davo basins clearly showed that a reduction in vegetation cover contributes to an increase in flows. In order to assess the impact of meteorological drought on flows, a correlative analysis was carried out between meteorological (SPEI) and hydrological (SDI) drought indices at the Daloa, Vavoua and Zuénoula stations.…”
mentioning
confidence: 99%